Dietary Vitamin D Increases Percentages and Function of Regulatory T Cells in the Skin-Draining Lymph Nodes and Suppresses Dermal Inflammation. (8th September 2016) - Gorman, Shelley; Geldenhuys, Sian; Judge, Melinda; Weeden, Clare E.; Waithman, Jason; Hart, Prue H.
Abstract : Skin inflammatory responses in individuals with allergic dermatitis may be suppressed by dietary vitamin D through induction and upregulation of the suppressive activity of regulatory T (T R e g ) cells. Vitamin D may also promote T R e g cell tropism to dermal sites. In the current study, we examined the capacity of dietary vitamin D3 to modulate skin inflammation and the numbers and activity of T R e g cells in skin and other sites including lungs, spleen, and blood. In female BALB/c mice, dietary vitamin D3 suppressed the effector phase of a biphasic ear swelling response induced by dinitrofluorobenzene in comparison vitamin D3 -deficient female BALB/c mice. Vitamin D3 increased the percentage of T R e g (CD3+CD4+CD25+Foxp3+) cells in the skin-draining lymph nodes (SDLN). The suppressive activity of T R e g cells in the SDLN, mesenteric lymph nodes, spleen, and blood was upregulated by vitamin D3 . However, there was no difference in the expression of the naturally occurring T R e g cell marker, neuropilin, nor the expression of CCR4 or CCR10 (skin-tropic chemokine receptors) on T R e g cells in skin, SDLN, lungs, and airway-draining lymph nodes. These data suggest that dietary vitamin D3 increased the percentages and suppressive activity of T R e g cells in the SDLN, which are poised to suppress dermal inflammation.